Penelitian dan Pengembangan Sistem Mutu Akuntansi Keuangan Pada Usaha Ternak Ayam Potong Blitar - Defia Nurbatin; Hendy Hermawan (Akuntansi dan Teknologi Informasi, 2018)
Abstract The purpose of this research is to arrange guidance of recording to financial reporting as model of development of financial accounting quality system at Cak Wanto chicken farm in Blitar. The method used in this research is the research & development model of DBR (Design Based Research) from Purwiyanto (2014) which is modified. Research phase starts from problem identification, data collection, product preparation, product test (expert validation) and final product refinement. Data collection techniques are Focus Group Discussion, observation, interview, and questionnaire (questionnaire). Questionnaire as an expert validation instrument consists of 4 aspects of the assessment of aspects of usability, convenience, completeness, and legibility. Techniques used to analyze data validation scoring results is to use a percentage technique with the category of interval Before-After technique. This study produces a quality system in the form of three SOPs that show the application of SOP can run effectively to be implemented with evidence of the average percentage results near perfect and in accordance with user needs. Keywords: Quality Accounting System, Standard Operating Procedures